Counseling on The Danger of HIV/AIDs Disease to Junior High School (SMP) Students Slam Miftahul Ulum - Saipul Wakit; Margiyono Suyitno (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
HIV/AIDs is a disease that can have a negative impact on sufferers. As many studies have shown, this disease is difficult to cure. Quantitatively, HIV/AOD sufferers in Indonesia have increased from year to year with varying degrees of cases. These factors are due to promiscuous sexual relations, changing partners frequently, a healthy lifestyle that is not implemented properly, and because of moral degradation in society. The aim of community service activities is to provide knowledge and skills to students about HIV/AIDs, as well as efforts to prevent this disease. Practically providing education with a preventive approach in preventing and treating HIV/AIDs for students. This activity method goes through three stages, namely preparation by providing a place, materials, facilitators, preparing supporting equipment and asking the school principal for permission for the activity. After that, socialization activities were carried out to students using lecture, question and answer and discussion methods. For evaluation, a pre-test and post-test are carried out at the end of the activity. The results of the activities provide information that quantitatively there is an increase in knowledge about HIV/AIDs by 42%, while knowledge of efforts to prevent HIV/AIDs is 50% and skills in controlling transmission are 42%. Qualitatively, it can be concluded that students increased in aspects of their knowledge and skills about HIV/AIDs after participating in socialization activities.